Efektivitas Insersi Caring Economics Pada Pembelajaran Kewirausahaan Dalam Menumbuhkan Minat Sociopreneur Di Universitas PGRI Wiranegara - Suchaina, Suchaina; Pradikto, Sugeng; Shalikha, Putri Ayu Anisatus (Universitas Hamzanwadi, 2023)
Entrepreneurship education is often identified as a business learning that focuses on building networks and developing profitable business plans. However, it often neglects to teach the students about how their business can be beneficial and impactful for the surrounding community. Therefore, there is a need to incorporate caring economics into entrepreneurship education to cultivate an interest in becoming a sociopreneur, where sociopreneurs are considered capable of addressing social issues such as poverty. The aim of this research is to determine the effectiveness of incorporating caring economics into entrepreneurship education and fostering a sociopreneurial to the students. The research method employed in this study is quasi-experimental, involving only one group without a control group, consisting of 32 students taking entrepreneurship courses. The instruments used include pretests and post-tests to assess the significance of the effectiveness of the caring economics incorporation. Additionally, a questionnaire is utilized to measure the interest in becoming a sociopreneur. The research findings indicate that based on the significance test of pretests and post-tests, the incorporation of caring economics shows a significant difference in the average understanding of students regarding the importance of caring economics in entrepreneurship education. However, the results regarding the interest in entrepreneurship based on caring economics and the interest in becoming a sociopreneur are still in the moderate category